DAMAGE ANALYSIS OF INSULATED PIPES USING DIGITAL DETECTOR ARRAY DAN COMPUTED RADIOGRAPHY - Tjahjono, Arif; Pratama, Elfriani Dita; Hanuarjie, Baskan; Saptari, Sitti Ahmiatri; Kumila, Biaunik Niski (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2025)
The provision of insulation on the pipe functions to prevent heat transfer, but the provision of this insulation causes the pipe to be susceptible to damage due to oxidation. In this study, an analysis of damage to insulated pipes will be carried out using a Digital Detector Array (DDA), Computed Radiography (CR), and XRF. Based on the test results, it is known that the image quality using DDA with a voltage of 240 kV produces the most optimal contrast resolution. The results of the thickness dimension measurement using the DDA method on insulated pipes are 3.38 mm, and on insulated pipes with artificial defects are 4 mm. Compared with the CR method, the values are 3.02 mm and 3.94 mm, respectively. The smaller the difference, the more accurate. From the calculation of the ISee software, it is also known that the DDA method can detect a greater number of defects, namely 24, compared to the CR method, which has only 14. The results of the XRF test show that the insulated pipe includes low-carbon steel with a carbon content of 0.057% and 94% ferrum. This high ferrous content contributes to increased X-ray absorption, greatly affecting the images quality.